2023
DOI: 10.1039/d2mh01527g
|View full text |Cite
|
Sign up to set email alerts
|

Interface-related phenomena in epitaxial complex oxide ferroics across different thin film platforms: opportunities and challenges

Abstract: Interfaces in complex oxides give rise to fascinating new physical phenomena arising from the interconnected spin, lattice, charge and orbital degrees of freedom. Most commonly, interfaces are engineered in epitaxial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 238 publications
0
3
0
Order By: Relevance
“…Self-assembled metal-oxide nanocomposites have generated tremendous research interest due to their fascinating functionalities and potential applications in the fields of energy harvesting devices, catalysis, magnetic data storage, and optical metamaterials. Among them, vertically aligned nanocomposites (VAN) with metal nanopillars embedded in an oxide matrix have attracted much attention because of their vertical strain coupling, strong structural and property anisotropy, enabling the epitaxial growth of large mismatched systems, and versatile material combinations coupling spin, charge, lattice, and orbital degrees of freedom. , However, due to the limited understanding of the growth kinetics in the self-assembly VAN growth process, controlling the morphology of the formed nanopillars by simply tuning the deposition parameters is usually difficult. Very uniform pillar distribution and density tuning have been demonstrated in multiple VAN systems, but with limited success in achieving ordering and morphology control of nanopillars. Lu et al demonstrated initial success in in-plane long-range ordering in the La 0.7 Sr 0.3 MnO 3 -Au system on annealed SrTiO 3 (STO) substrates with well-controlled terraces for nucleation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembled metal-oxide nanocomposites have generated tremendous research interest due to their fascinating functionalities and potential applications in the fields of energy harvesting devices, catalysis, magnetic data storage, and optical metamaterials. Among them, vertically aligned nanocomposites (VAN) with metal nanopillars embedded in an oxide matrix have attracted much attention because of their vertical strain coupling, strong structural and property anisotropy, enabling the epitaxial growth of large mismatched systems, and versatile material combinations coupling spin, charge, lattice, and orbital degrees of freedom. , However, due to the limited understanding of the growth kinetics in the self-assembly VAN growth process, controlling the morphology of the formed nanopillars by simply tuning the deposition parameters is usually difficult. Very uniform pillar distribution and density tuning have been demonstrated in multiple VAN systems, but with limited success in achieving ordering and morphology control of nanopillars. Lu et al demonstrated initial success in in-plane long-range ordering in the La 0.7 Sr 0.3 MnO 3 -Au system on annealed SrTiO 3 (STO) substrates with well-controlled terraces for nucleation .…”
Section: Introductionmentioning
confidence: 99%
“… 1 8 Among them, vertically aligned nanocomposites (VAN) with metal nanopillars embedded in an oxide matrix have attracted much attention because of their vertical strain coupling, strong structural and property anisotropy, enabling the epitaxial growth of large mismatched systems, and versatile material combinations coupling spin, charge, lattice, and orbital degrees of freedom. 9 , 10 However, due to the limited understanding of the growth kinetics in the self-assembly VAN growth process, controlling the morphology of the formed nanopillars by simply tuning the deposition parameters is usually difficult. Very uniform pillar distribution and density tuning have been demonstrated in multiple VAN systems, but with limited success in achieving ordering and morphology control of nanopillars.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the superior radiation tolerance, perovskite oxide films, especially lead-based series films, such as PbTiO 3 , Pb­(Zr 1– x Ti x )­O 3 , and 0.7Pb­(Mg 1/3 Nb 2/3 )­O 3 -0.3PbTiO 3 , are widely used as piezoelectric sensors, field effect transistors, and ferroelectric random access memories in harsh environments. As one of the applications of lead-based materials, Lamb-wave-based structural health monitoring (SHM) systems rely on Pb­(Zr 1– x Ti x )­O 3 piezoelectric ceramics to excite and receive Lamb-wave response signals before and after damage occurs, thereby detecting damage and ensuring the safety of aerospace vehicles. However, the rigid and fixed dimensions of Pb­(Zr 1– x Ti x )­O 3 ceramics hinder their application in damage monitoring on complex curved structures. And a heavy burden is brought to the aerospace vehicle by the weight of the Pb­(Zr 1– x Ti x )­O 3 ceramic network.…”
Section: Introductionmentioning
confidence: 99%